Network Neutrality on the Internet: A Two-sided Market Analysis - Nicholas Economides; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2008)
We discuss the benefits of net neutrality regulation in the context of a two-sided market model in which platforms sell Internet access services to consumers and may set fees to content and applications providers on the other side of the Internet. When access is monopolized, we find that generally net neutrality regulation (that imposes zero fees on the other side of the market) increases total industry surplus compared to the fully private optimum at which the monopoly platform imposes positive fees on content and applications providers. Similarly, we find that imposing net neutrality in duopoly increases total surplus compared to duopoly competition between platforms that charge positive fees on content providers. We also discuss the incentives of duopolists to collude in setting the fees on the other side of the Internet while competing for Internet access customers. Additionally, we discuss how price and non-price discrimination strategies may be used once net neutrality is abolished. Finally, we discuss how the results generalize to other two-sided markets.
Keywords: C63; D40; D42; D43; L10; L12; L13; 330; Net Neutrality; Two-sided Markets; Internet; Monopoly; Duopoly; Regulation; Discrimination; Internet; Breitbandkommunikation; Netzregulierung; Regulierung; Marktstruktur; Theorie